The English A Foreign Language Students' English Long and Short Vowel Pronunciation - Tahang, Heriyanti; Hardianti, Rinda; Winarti, Etik; Salsabila, Nanda Annisa; Said, Dian Riani (JULIET: Journal of English Language and Literature, 2024)
This article aimed to find out what vowel sounds were difficult to pronounce by the students of the third semester at the University of Muhammadiyah Sorong. It employed a descriptive method that provided an oral test of 25 words as the instrument. The research subjects were the third-semester students of the English Language Education program at University of Muhammadiyah Sorong. It had 20 study participants. The data was gathered via oral tests and examined qualitatively. According to the study's findings, students in the third semester at the University of Muhammadiyah Sorong had the most difficult time pronouncing two English vowels. Students struggled to pronounce the long vowel /i:/ in "key" and the short vowel /Λ/ in "done". Based on this research, it is suggested that the English Pronunciation Lecture teaches vowels in more detail. The students should learn vowels seriously, and the next researcher should research the pronunciation of more than one syllable.